The NanDeSyn database for Nannochloropsis systems and synthetic biology. (27th November 2020) - Gong, Yanhai; Kang, Nam K.; Kim, Young U.; Wang, Zengbin; Wei, Li; Xin, Yi; Shen, Chen; Wang, Qintao; You, Wuxin; Lim, Jong‐Min; Jeong, Suk‐Won; Park, Youn‐Il; et al.
Summary: Nannochloropsis species, unicellular industrial oleaginous microalgae, are model organisms for microalgal systems and synthetic biology. To facilitate community‐based annotation and mining of the rapidly accumulating functional genomics resources, we have initiated an international consortium and present a comprehensive multi‐omics resource database named Nannochloropsis Design and Synthesis (NanDeSyn; http://nandesyn.single‐cell.cn ). Via the Tripal toolkit, it features user‐friendly interfaces hosting genomic resources with gene annotations and transcriptomic and proteomic data for six Nannochloropsis species, including two updated genomes of Nannochloropsis oceanica IMET1 and Nannochloropsis salina CCMP1776. Toolboxes for search, Blast, synteny view, enrichment analysis, metabolic pathway analysis, a genome browser, etc. are also included. In addition, functional validation of genes is indicated based on phenotypes of mutants and relevant bibliography. Furthermore, epigenomic resources are also incorporated, especially for sequencing of small RNAs including microRNAs and circular RNAs. Such comprehensive and integrated landscapes of Nannochloropsis genomics and epigenomics will promote and accelerate community efforts in systems and synthetic biology of these industrially important microalgae. Significance Statement: Nannochloropsis species have emerged as model organisms for microalgal systems and synthetic biology, but a centralized portal to store, mine and disseminate the rapidly expanding multi‐omics datasets is lacking. Here, we initiate an international consortium and present a comprehensive resource database named Nannochloropsis Design and Synthesis (NanDeSyn; http://nandesyn.single‐cell.cn ). NanDeSyn hosts genomic and epigenomic resources such as gene annotation, transcriptome, proteome, small RNA and mutant information, and provides tools for search, Blast, synteny view, enrichment analysis, metabolic pathway analysis and a genome browser.